LINKING SOCIAL MEDIA COMMERCE, MARKET ORIENTATION, AND MSME PERFORMANCE: EMPIRICAL EVIDENCE FROM TANAH ABANG, JAKARTA - Lubis, Asep Ridwan; Kurniati, Fitrina; Rohayati, Yuyun (MIMBAR PENDIDIKAN, 2025)
This study examines the relationship between social media commerce, market orientation, and MSME performance in Indonesia's fashion industry, specifically investigating market orientation's mediating role. Using a quantitative cross-sectional approach, data was collected from 100 fashion MSMEs in Tanah Abang Market, Jakarta, who actively utilize TikTok Shop. Path analysis with SPSS revealed significant positive relationships across all hypotheses. Social commerce directly influences MSME performance (β = 0.172, p = 0.045) and enhances market orientation capabilities (β = 0.263, p 0.05). Market orientation significantly drives performance improvements (β = 0.253, p = 0.005), while partially mediating the social commerce-performance relationship (indirect effect = 0.066). The combined model explains 37.7% of performance variance, demonstrating dual value creation mechanisms wherein social commerce generates benefits through direct platform advantages and enhanced market-sensing capabilities. The findings contribute to social commerce literature by providing empirical evidence from emerging markets and identifying market orientation as a key mediating mechanism. Practically, successful social commerce implementation requires integrated approaches combining platform adoption with systematic market orientation development. MSMEs should leverage analytics for customer understanding, utilize interactive features for market intelligence, and develop competitive monitoring to maximize benefits. The study positions social commerce as a strategic imperative rather than merely technological adoption, serving dual functions as transactional channels and capability-building tools for sustainable competitive advantage.